Kualitas Pelayanan Pendaftaran Tanah Sistematis Lengkap di Badan Pertanahan Nasional Kota Batu - Deka, Rio Era; Ilyas, Taufiq Rahman (Jurnal Ilmiah Global Education, 2025)
Complete Systematic Land Registration (PTSL) is an Indonesian government program that aims to accelerate the land registration process in all regions. The quality of the Complete Systematic Land Registration Program (PTSL) in Batu City is alleged to have failed in achieving the goals that have been set. and (4) the main outcome of the discussion. The research method used in this study is a descriptive method with a qualitative approach. Data collection consists of observations and interviews and is used as a model to determine the quality of PTSL program services in Batu City. The dimensions of tangibles, reability, assurance, responsiveness, and empathy are components of the PTSL service quality assessment measurement instrument